1992
DOI: 10.1111/j.1349-7006.1992.tb02734.x
|View full text |Cite
|
Sign up to set email alerts
|

Oligonucleotide Sequences Required for Natural Killer Cell Activation

Abstract: Based on the previous finding that certain 30‐mer single‐stranded oligodeoxyribonucleotides (oligonucleotides) having particular 6‐mer palindromic sequences could induce interferon‐alpha and ‐gamma, and enhance natural killer activity, the present study was carried out to clarify the entire relationship between the activity and the sequence of 30‐mer oligonucleotides. The results indicated that the activity depended critically on the presence of particular palindromic sequences including the 5 ‐CG‐3 motif(s). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
45
0

Year Published

1996
1996
2015
2015

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 117 publications
(45 citation statements)
references
References 14 publications
0
45
0
Order By: Relevance
“…Such studies have included both in vitro assays and, to a lesser extent, in vivo animal models. Furthermore, it has been suggested that the antitumor activity exerted by some phosphorothioate ODNs may be due to either a non-sequence-related effect of ODNs on binding to specific growth factors or a sequencespecific effect of ODNs on stimulation of natural killer cell activity in host animals (16)(17)(18)(19)(20). These reports, as well as others (2,14,15), demonstrate the need to rigorously examine the mechanism of action of a particular ODN before concluding that the pharmacological effects exerted by that ODN are derived from an antisense mechanism of action.…”
Section: Discussionmentioning
confidence: 99%
“…Such studies have included both in vitro assays and, to a lesser extent, in vivo animal models. Furthermore, it has been suggested that the antitumor activity exerted by some phosphorothioate ODNs may be due to either a non-sequence-related effect of ODNs on binding to specific growth factors or a sequencespecific effect of ODNs on stimulation of natural killer cell activity in host animals (16)(17)(18)(19)(20). These reports, as well as others (2,14,15), demonstrate the need to rigorously examine the mechanism of action of a particular ODN before concluding that the pharmacological effects exerted by that ODN are derived from an antisense mechanism of action.…”
Section: Discussionmentioning
confidence: 99%
“…Because the GACGATCGTC sequence exists in the bacterial genomes, with various numbers of G on each side, we used the pal-GACGA1010 in unmodified phosphodiester form as a counterpart of bacterial DNA, which has previously been shown to have immunostimulatory activity in mice and humans (14,32).…”
Section: Cpg Dna Induces Human Pdcs To Express Cxcl10 and Ccl3 In Addmentioning
confidence: 99%
“…It is well known that bacterial DNA and synthetic oligodeoxynucleotides (ODNs) containing specific motifs centered on a CpG dinucleotide (CpG ODNs) are potent immunostimulatory agents (1)(2)(3)(4)(5). Unmethylated CpG sequences are present at a frequency of 1 in every 16 dinucleotides in bacteria, while mammals have a CG dinucleotide suppression with only one-fourth of the expected frequency, and the majority of the CpG sequences are methylated in mammals (6).…”
mentioning
confidence: 99%